Design and Research on the Drilling and Lifting Device of Coalbed Methane Drilling Machine - Liu, Qi (E3S web of conferences, 2024)
In response to the problems of complex operation procedures, long auxiliary time, and impact on drilling efficiency in coalbed methane drilling construction, a fast tripping and lifting device for coalbed methane drilling rig is designed. The device has a compact and reasonable structure, and strong process adaptability; The structure of clamping with a wedge-shaped groove and releasing the basket is used. In the drilling operation of the drill-ing rig, the drilling rod is clamped with a lifting device instead of a threaded connection, and the lifting and lowering of the drilling rod is completed with the help of a rotator. The operation is simple, reducing auxiliary time and improving drilling efficiency. Simultaneously using a self sealing floating core tube structure and hydraulic pressurization, the sealing between the lift-ing device and the drilling tool can be achieved. During drilling operations, mud can be directly introduced for drilling, improving the ability to handle drilling accidents.